The Dilemma of Innovative Behavior of Hybrid Entrepreneurs in the Role of Employees - Tyna Yunita; Murti Wijayanti; Eri Bukhari; Ery Teguh Prasetyo (Universitas Proklamasi 45, 2022)
Innovation is a crucial element to achieving business success and sustainability. In pursuing superior performance, organizational members generate new ideas and realize new ideas. Hybrid entrepreneurship was a phenomenal point of view but was still poorly studied in the management literature. This research that examines the topic of entrepreneurship contributes to the development of entrepreneurship and economic growth. The approach in this research was quantitative. Respondents were entrepreneurs and employees in the Greater Jakarta area (Jabodetabek) with a simple random sampling technique. A total of 104 respondents returned the questionnaire. Evaluation of research hypotheses used SmartPLS software program. Results show that all variables have a significant correlation.